Trace elements in sediments of two lakes in the valley of the middle courses of the Ob River (Western Siberia) - Shevchenko, Vladimir P.; Starodymova, Dina P.; Vorobyev, Sergey N. биолог; Aliev, Ramiz A.; Borilo, Lyudmila P.; Kolesnichenko, Larisa G.; Lim, Artem G.; Osipov, Andrey I.; Trufanov, Vladislav V.; Pokrovsky, Oleg S. (Minerals)
Lake sediments accumulate various pollutants and act as efficient natural archives suitable for reconstruction the environmental conditions of the past. In contrast to fairly good knowledge of mineral sediments in lakes of European and North America boreal lakes, Siberian lakes of the boreal zone remain quite poorly studied. In this work, two cores of lake sediments of the Ob River valley were investigated. Elemental analyses were carried out on the sediments, losses on ignition were determined, and the rate of sedimentation was measured from the activity of Pb-210 and Cs-137. According to the content of organic matter, bottom sediments belong to different types: clastic (Lake Inkino, located in the Ob River floodplain) and organogenic (Lake Shchuchie on the second terrace). The rate of sedimentation in Lake Shchuchie is several times higher than that in Lake Inkino. The sediments of Lake Inkino are similar in composition (including the pattern of rare earth elements) to the suspended particulate matter of the Ob River as well as to average detrital matter of the upper continental crust. Sediments of Lake Shchuchie (sapropels) are enriched in a number of heavy metals. Based on the elemental composition, signs of diagenetic processes and authigenic mineral formation were determined, such as accumulation of carbonates and the formation of manganese oxides and hydroxides. There is an enhanced recent input of Cr, Co, Cu, Zn, Cd, Sb, Pb, and Bi in the upper layers of sediments as a result of atmospheric anthropogenic pollutant deposition.